Unprotected left main coronary artery stenting: true vs. non true bifurcation lesions; a single-centre experience. (14th October 2021) - Santucci, A; Scavelli, F; Jacoangeli, F; Mattei, C; Sclafani, R; Notaristefano, S; Bordoni, E; Aimi, A; Cavallini, C
Abstract: Aims: We investigated the impact of bifurcation lesions involving a side branch lesion combined with a main branch stenosis on clinical outcomes after percutaneous coronary intervention (PCI) on unprotected left main coronary artery (ULM). Methods and results: We defined "true" bifurcation lesions as significant (>50%) side branch stenosis associated with a significant main branch lesion, either proximal or distal, according to the Medina classification (1.1.1, 1.0.1 or 0.1.1 lesions). "Non true" lesions were defined by absence of significant side lesions, or significant side lesions without concomitant main branch stenosis. We compared patients with "non-true" bifurcation lesions (N=132; 56%) with those with "true" bifurcation lesions (N=105; 44%) in their 12-month incidence of target vessel failure (TVF) (composite of (i) cardiac death related to target vessel; (ii) myocardial infarction related to target vessel, or (iii) ischemia-driven target vessel revascularization), death from any cause, target lesion revascularization (TLR) and stent thrombosis (ST). TVF occurred in 56 patients (24%) (figure 1). Patients with "true" bifurcation lesions had a significantly higher risk of TVF than those with "non-true" bifurcation lesions (HR 2.39; 95% CI 1.39–4.11, P=0.002). "True" bifurcation lesions were also associated with a higher risk of all cause of death (HR, 2.54; 95% CI, 1.09–5.94; P=0.031) and TLR (HR, 2.33; 95% CI, 1.1–4.94, P=0.027). 'True' bifurcation lesions, diabetes mellitus, as well as cardiogenic shock, were independently associated with an increased risk of TVF (figure 2). Of note, the SYNTAX score I was not identified as an independent predictor of TVF. The stenting strategy (1 vs 2 stents) did not show any significant association with the outcome. Conclusions: Patients with ULM and "true" bifurcation lesions who undergo PCI have a worse clinical outcome than those with "non-true" bifurcation lesions. Funding Acknowledgement: Type of funding sources: None.